E-ARSIP BAGI LEMBAGA PENDIDIKAN BERBASIS WEB MENGGUNAKAN FRAMEWORK CODEIGNITER - Nahdliy, Faiz Jabar; Fatkhurrochman, Fatkhurrochman; Kapti, Kapti; Muin, Muhammad Abdul; Wahyudiono, Sugeng; Handayani, Riska Dwi (STMIK BINA PATRIA, 2024)
Technology helps users do various things and activities that can produce the latest and innovative technology in various fields, including education. MTs Ma'arif Tembarak is a formal secondary level educational institution under the Ministry of Religion in Temanggung Regency. In carrying out archive management still using conventional methods and has not digitized archives, with 1,500 archive data recorded over 3 years. This causes uncertainty in archival documents and the history of follow-up to managed documents as well as difficulty in searching for data and documents. This research aims to design and build a web-based e-archive system for educational institutions to provide solutions to the problems faced. The method in this research uses the waterfall method with system visualization using DFD and ERD in the database management illustration used. The e-archive system was developed on a web basis with PHP and MySQL programming languages using the CodeIgniter framework and tested using the black box testing method with valid results. Next, a user evaluation was carried out on 5 respondents according to user level with the results of the feasibility percentage being 72%, based on the Likert scale, it was said that the impact or use value was good.